2017
DOI: 10.17219/acem/63025
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Weight Loss Induced by Metformin is Independently Associated with BMI at Baseline in Newly Diagnosed Type 2 Diabetes: Post-hoc Analysis from Data of a Phase IV Open-labeled Trial

Abstract: Background. The impact of metformin on body weight is variable in T2DM patients among studies. The reasons for the discrepancies are still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…1 In the paper to be discussed in this installment of the Journal of Parenteral and Enteral Nutrition Journal Club, Zhou et al attempt to provide more details about this phenomeonon. 2 The data came from a retrospective analysis of a prospective, uncontrolled, observational study that was reported in 2013. 3 In that original study, newly diagnosed adult diabetics who were treatment naive were enrolled in an uncontrolled 3-arm study; patients were assigned to the groups depending on whether they were classified as normal, overweight, or obese, according to their baseline body mass index (BMI, kg/m 2 ).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1 In the paper to be discussed in this installment of the Journal of Parenteral and Enteral Nutrition Journal Club, Zhou et al attempt to provide more details about this phenomeonon. 2 The data came from a retrospective analysis of a prospective, uncontrolled, observational study that was reported in 2013. 3 In that original study, newly diagnosed adult diabetics who were treatment naive were enrolled in an uncontrolled 3-arm study; patients were assigned to the groups depending on whether they were classified as normal, overweight, or obese, according to their baseline body mass index (BMI, kg/m 2 ).…”
mentioning
confidence: 99%
“…Thus, the remaining results consisted of comparisons between the 4 quartiles of weight loss. Zhou et al began by trying to provide the clinical characteristics of the groups, but only those of 3 of the groups were tabulated 2 ; the details of group 4 (those with the greatest weight loss) were not included in that table. The text of the paper indicated that, compared with the group with the lowest weight loss, those with the greatest weight loss had significant associations with 4 baseline characteristics (heaviest weight, highest BMI, largest waistline, and lowest serum albumin level).…”
mentioning
confidence: 99%
See 3 more Smart Citations